Instalación y configuración de software open source para monitorear el servicio y la carga de un sistema asterisk - Borbor, William (2009)
The present work is the development of a technological solution based on the study, use and management of an open source monitoring software with which to take permanent control over a central phone server performance Asterisk platform as well as all services of the same to avoid possible mistakes and making improvements in the VOIP. This solution could be used in any enterprise that has implemented a central telephone with Asterisk, therefore has great potential to be marketed, besides having a projection monitor any communication channel. Nagios software was selected from a wide variety and it can monitor the entire IT infrastructure to ensure that systems, applications, services and business processes are functioning properly. In the event of a failure Nagios can alert technical staff of the problem, which would initiate appropriate corrective measures, rather than failures affecting business processes, end users or customers. The more important services of asterisk server are monitored with Nagios system are: Performance CPU, RAM, Channels Asterisk SIP, IAX, DAHDI, active calls and Bandwidth.